The Nature Of Proof And Evidence According To Positive Law - Aryasyahdanu; Syahdan Ivander Bayu; Muhammad Amir Saragih; Desy Rahma Sari Sitorus Pane (ISNU Nine-Star Multidisciplinary Journal, 2024)
This study discusses the application of evidentiary law and evidence in the State Administrative Court (PTUN). The background of this study is based on the importance of the role of evidence in the trial process to determine the validity of administrative decisions. This study uses a normative legal method with a statutory regulatory approach and case studies. The research stages include an analysis of laws related to evidence in the PTUN as well as a study of cases that have been decided by the court. The results of the study indicate that evidentiary law in the PTUN relies heavily on written evidence, especially documents issued by state administrative officials. Although electronic evidence is legally recognized, its application is still limited due to doubts about the authenticity and security of digital data. In addition, witness statements, confessions, and oaths are used minimally, and the role of this evidence tends to only complement written evidence. The discussion in this study highlights the challenges in the application of evidentiary law in the PTUN, including accessibility to documents and the acceptance of electronic evidence. In conclusion, although the evidentiary process in the PTUN is effective, there needs to be an increase in the use of electronic evidence and optimization of non-document evidence to improve efficiency and fairness in the trial process.